Synchronous Bilateral Breast Carcinoma and Axillary Non-Hodgkin Lymphoma: A Case Report and Review of the Literature - Miles, Edward F. (Hindawi Publishing Corporation, 2012)
The use of staging imaging modalities with increased sensitivity has led to an increase in the incidence of detection of simultaneous malignancies. These cases require careful evaluation and discussion in a multidisciplinary setting to establish a treatment plan that optimizes the outcome with respect to each malignancy, particularly when treatment modalities overlap. We report a case of a patient diagnosed with axillary nodal diffuse large B-cell lymphoma (DLBCL) in a community hospital where staging workup also revealed synchronous bilateral breast carcinomas. To our knowledge, this is only the second case report of a patient with three synchronous primary malignancies: bilateral breast carcinomas and axillary DLBCL. The only other similar case report had no role for radiation or chemotherapy in the management of the indolent follicular lymphoma.